2021
DOI: 10.1177/0969733021996028
|View full text |Cite
|
Sign up to set email alerts
|

Moral distress among nurses: A mixed-methods study

Abstract: Background: Moral distress is recognized as a problem affecting healthcare professionals globally. Unaddressed moral distress may lead to withdrawal from the moral dimensions of patient care, burnout, or leaving the profession. Despite the importance, studies related to moral distress are scant in Thailand. Objective: This study aims to describe the experience of moral distress and related factors among Thai nurses. Design: A convergent parallel mixed-methods design was used. The quantitative and qualitative d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(57 citation statements)
references
References 55 publications
0
44
0
Order By: Relevance
“…Studies were conducted in ten countries: UK (n=14),37–50 Australia (n=6),51–56 USA (n=5),57–61 Sweden (n=5),62–66 Canada (n=4),67–70 New Zealand (n=2),71 72 Saudi Arabia (n=1),73 the Netherlands (n=1),74 Thailand (n=1)75 and China (n=1) 76. Years of publication ranged from 2001 to 2021.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies were conducted in ten countries: UK (n=14),37–50 Australia (n=6),51–56 USA (n=5),57–61 Sweden (n=5),62–66 Canada (n=4),67–70 New Zealand (n=2),71 72 Saudi Arabia (n=1),73 the Netherlands (n=1),74 Thailand (n=1)75 and China (n=1) 76. Years of publication ranged from 2001 to 2021.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies reported having conducted a general analysis of themes (n=22) 37–43 45–49 55 60 61 64 67 68 70 72–74. Content analysis51–54 56 57 62 65 66 76 and thematic analysis involving specific frameworks were conducted as well 44 50 58 59 69 75. Other methods included narrative analysis,63 basic descriptive analysis71 and matrix analysis 59…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations